MULCHING AND ROW COVER IN LETTUCE CROP - REGHIN, Marie Yamamoto; PURISSIMO, Claudio; FELTRIM, Anderson Luiz; FOLTRAN, Marco Aurélio (Scientia Agraria, 2002)
An experiment was conducted in Ponta Grossa, Paraná, Brazil, in order to evaluate mulching materials and row cover with polypropylene. The experimental design was a randomized complete block with five replications. Treatments were arranged in a factorial scheme 3x2 (mulching with black polypropylene, rice straw and bare soil; row cover with white polypropylene and no row cover). Seeds were sowed in 05/02/01 and the plantlets transplanted in 06/01/01. Perforated black polypropylene mulch was placed on the plots before plantlet transplanting, while rice straw was placed after transplanting. White polypropylene was used as row cover. At harvesting, lettuce total leaf number, frost damaged leaves, plant height, stem lenght; plant fresh weight, plant dry matter of plant, and biomass, were evaluated. In addition, weed population and weed dry weight were assessed. Row cover with white polypropylene provided positive response on lettuce yield, with early harvest and high quality and commercial plant characteristics, even with frost occurrence. Frost damage in plots without row cover reduced plant weight by 34,62%. Black poplypropylene mulch controlled weeds and provided 22,12% increase on plant weight compared to rice straw.